The CAVERN study: a randomised comparison of CartoMerge and NavX fusion in catheter ablation of atrial fibrillation. (22nd September 2015) - Finlay, MC; Richmond, L; Rajappan, K; Earley, MJ; Liew, R; Thomas, G; Tenkorang, J; Hunter, R; Baker, V; Goromonzi, F; Sporton, S; Dhinoja, M; et al.
Abstract : Introduction: Integration of a 3D reconstruction of the left atrium (CTLA) into cardiac mapping systems may improve the efficacy of catheter ablation of atrial fibrillation (AF). We performed a randomised trial of NavX fusion versus CartoMerge in patients undergoing their first catheter ablation. Methods: Patients undergoing their first catheter ablation were randomly assigned to mapping using NavX fusion or CartoMerge guided pulmonary vein isolation by wide area circumferential ablation for paroxysmal AF with additional linear and fractionated potential catheter ablation for persistent AF. Differences between groups were analysed using Graphpad Prism 4. The Mann–Whitney test was used to compare medians between groups, the log rank test was used to test survival, p<0.05 was considered significant. Results: 64 patients were recruited, the two groups had similar demographic characteristics. CartoMerge had significantly shorter CTLA registration time, screening for registration and x ray dose for registration (table). There was no difference in overall procedural times, screening times or radiofrequency timings between groups. There was a trend for lower radiofrequency doses with CartoMerge in isolating the right pulmonary veins and overall in persistent AF. Clinical outcomes, defined as freedom from arrhythmia, were similar between groups in paroxysmal AF patients, but patients with persistent AF mapped with NavX had greater recurrence (hazard ratio 0.35 (0.08 to 0.70)). Complications were similar in both groups. Conclusions: CartoMerge registration is quicker and requires less x ray use than NavX fusion. Overall, clinical results using the two systems are identical in patients with paroxysmal AF. In patients with persistent AF, CartoMerge was more effective and used lower radiofrequency doses. A feasible explanation would be loss of location accuracy in NavX due to artifact secondary to minor impedance change. This study suggests that CartoMerge may be superior to NavX in a subgroup of patients with persistent AF.